WOMAN’S STRUGGLE IN POLITICS AS REFLECTED IN MARGARET THATCHER’S CHARACTER IN THE MOVIE THE IRON LADY - MUNYROH, AFSHOCHUL (Jurnal Ilmiah Mahasiswa FIB, 2013)
Politics in England was dominated by men. This made the percentage of women in British parliament became low. That issue described in The Iron Lady film. This film explains about Margaret Thatcher’s struggle to break male domination in politics in England. This study used feminist approach and movie study to analyze The Iron Lady film. In this study, it is revealed that Margaret Thatcher is successful to break male domination on women in politics of England. She proves that women who are reputed as a weak creature and who are also underestimated by men can do the role which is commonly done by men. She started her struggle as a Conservative party’s member. After that she got a place in the British parliament as an education secretary. With her ambition to break male domination in politics, she put up herself to become the leader of Conservative party and finally she was became the first female British Prime Minister. Her success to uphold parliament and rule of law in England to some extent increased percentage of women who participated in British politics.